FEEDING NAPIER GRASS TO SMALL RUMINANT ANIMALS IN DRIER PARTS OF BAUCHI STATE AS A MITIGATION TO HERDER-FARMER CRISES - Gidado, A.S.; Sulaiman, R.; Jaafar, A.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The paper analyzed the feeding of Napier grass to small ruminant animals in the drier parts of Bauchi State as a mitigation to Farmer-Herder crises in Nigeria. The study was conducted using 16 growing Yankasa rams with an average weight of 17-16kg. Nutrient intake and growth performance were evaluated. The grass was chopped and fed ad libitum as basal diets with proteins and energy concentrates as supplements at different combinations designated as diets 1, 2, 3 and 4 respectively. The experiment was conducted in a completely randomized design (CRD) with each treatment having 4 animals. The basal diet and water were offered ad libitum while the concentrate diets were fed twice daily at the rate of 150g morning and afternoon each. Results show the basal diet intake (871.70-930.72g/day), total feed intake (1167.57-1219.85g/day), dry matter intake (1095.73-1221.00g/day) were not significant (p>0.005). However, supplement intake (g/day) was significant (p< 0.005) among the rams. Diet 4 recorded the highest intake value (295.87g/day) and the least value of (282.53g/day) was obtained from diet 2. However, the intake of crude proteins (113.06 and 109.46g/day) was significantly (p˂0.005) high for diet 1, and the lowest value (93.10g/day) was recorded for diet 2. Rams fed diet 4 recorded the highest final weights and average daily gain (ADG) of 23.50kg and 69.0g/day respectively while those on diet 1 had the least value (21.50kg and 65.2g/day). It was concluded that, feeding rams Napier grass supplemented with groundnut cake and maize bran concentrates gave better growth performance. Thus, feeding growing Yankasa rams chopped Napier diet, especially during the dry periods, along with 300g of groundnut cake and maize bran concentrates will go a long way to mitigate open grazing and Farmer-Herder conflicts in the study area, which is known for limited pasture and water sources, and in northern Nigeria generally.